(untitled) (Vanderbilt e-Journal of Luso-Hispanic Studies, 2016)
Friendship as an ideal and a social institution has long been associated with the eighteenth century, and viewed as essential to the betterment of society since it promoted sociability and relationships. This essay explores how the notions of silence and solitude, seemingly antithetical to friendship and sociability, were in fact complimentary activities which interfaced with the idea of amistad. In Spanish authors such as Forner, Moratín, Jovellanos and Meléndez Valdés, silence and solitude were represented as positive, necessary components, alongside friendship, in the acquisition of wisdom. I argue that these works articulate a brand of neo-Pythagoreanism, which romanticizes the archetype of the silent master and the contemplative ideal of the solitary thinker.